Renormalization Group Equation for Tsallis Statistics - Airton Deppman (Advances in High Energy Physics)
The nonextensive statistics proposed by Tsallis has found wide applicability, being present even in the description of experimental data from high energy collisions. A system with a fractal structure in its energy-momentum space, named thermofractal, was shown to be described thermodynamically by the nonextensive statistics. Due to the many common features between thermofractals and Hagedorn’s fireballs, this system offers the possibility of investigating the origins of nonextensivity in hadronic physics and in QCD. In this regard, the investigation of the scaling properties of thermofractals through the renormalization group equation, known as Callan–Symanzik equation, can be an interesting approach.